The Mystical Paradigm in Shakespeare’s King Lear - Potter, A. M. (Koers, 1993)
This article takes as its starting point the statement by Caroline Spurgeon that mysticism, with its aim of the union with the One, does not appear in Shakespeare's works. It is initially pointed out that any suggestion that mysticism is present in any work is fraught with serious reception problems, since mysticism is very adversely viewed at present, even by supposedly open-minded literary critics. After providing a definition of mysticism in terms which attempt to alleviate these reception problems, evidence will then be presented from King Lear to suggest that the play is built on the basis of an affirmation of unity, and a perception of disunity as resulting from the destructive effects of difference, division and duality. This, it is suggested, implies that Shakespeare was thinking in terms of the mystical paradigm when he wrote the play. In conclusion, some indication is given of possible significances of the presence of the mystical paradigm in the play, and how richly suggestive the presence of such a paradigm is in a play such as this.